DATA-DRIVEN INSIGHTS INTO LISTENING SKILLS: FUZZY C-MEANS CLUSTERING OF TEVOCS TEST TAKER PROFILES - Permatasari, Alfelia Nugky; Haryanto, Haryanto; Djidu, Hasan (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2024)
This article provides a comprehensive analysis of the Test of English for Vocational Students (TEVocS) Listening sections, which include 40 questions spread across four separate sections. The study encompasses a total of 866 participants, and the analytical methodology entails cluster analysis utilizing fuzzy C-means, which is executed through the R programming language. The main goals of this research are to categorize TEVocS test takers based on their English language proficiency, particularly in the area of listening abilities. The findings provide a detailed picture of the performance patterns among individuals taking the test, delivering significant insights for instructors to improve the listening proficiency of test takers.